Macroeconomics (Pearson education, 2015)
Errol D'Souza's Macroeconomics helps students realize the connections between theoretical frameworks and the actual behaviour of the economy; enables instructors to teach macroeconomics concepts within the context of both the Indian and global economy; and provides policymakers with material from current research in macroeconomics. The focus of the book rests on the analysis of macroeconomic thought in terms of the intuition and underlying logic that forms its basis. This book has been designed to help readers think independently about real-world situations, by helping them master the basic technical tools that enable them to do this. At a conceptual level, the book focuses on the most current and relevant issues, while also understanding the fluidity of the subject.